Fungsi Notaris Pejabat Pembuat Akta Tanah dalam Pelaksanaan Perjanjian Kredit Perbankan - S. Endang Prasetyawati (PRANATA HUKUM, 2016)
Notary services, is needed in deed bank credit agreements involving the customer and the bank, in order to ensure the correctness of the contents were poured into the bank credit agreement, to publicly truth is not in doubt. The research problem is how the functions of Notary or Land Deed Officer in the implementation of the bank credit agreement and how the force of law deed of bank credit agreement made by the Notary or Land Deed Officer. The research method in juridical normative and empirical is used primary and secondary data, and data analysis with qualitative analysis. The survey results revealed that the function of Notary / Land Deed Officer in Implementing Credit Agreement is a deed in accordance Orders of the bank where such orders have been agreed by the debtor (authentic deed). In addition, the notary as a person (figure) descriptive captions reliable, whose signatures and capnya guarantees and compelling evidence. Banks should do the legalization Notary if there is a loan agreement made in the form at the bottom of the hand.